Effect of different stages on match outcomes during high level judo competitions (Revista de Artes Marciales Asiáticas, 2020)
This study aimed to demonstrate the effect of successive stages of high-level judo competitions on match outcome and the factors effecting it. A total of 4550 official matches in both men and women were included in the analysis. Frequencies and percentages were used for descriptive statistics. Mean and standard deviations with 95% confidence intervals were also presented. The difference in the variables investigated for each stage of judo competitions was analysed with the Chi-square test. Continuous variables were analysed with the Kruskal-Wallis test. The way competitors won a match differed in elimination, final stages, and medal matches (p=.02). When the difficulty of the matches increased, the percentage of the matches ended with ippon decreased and the percentage of the matches resulted with waza-ari increased. The percentage of the matches without any shido decreased from the elimination to the finals while there was a significant increase in the percentage of the matches with shido (p=.01). The match duration was found to increase from eliminations to the finals (p=.00). The efficiency index of the winner athletes during the first stage was higher than the other stages (p